2003
DOI: 10.1016/s0002-9440(10)63442-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bcl-2 and Bcl-xL in Cutaneous and Bone Marrow Lesions of Mastocytosis

Abstract: Mastocytosis is a rare disease characterized by accumulation of mast cells in tissues.To investigate whether an altered regulation of mast cell apoptosis might be involved in the pathogenesis of mastocytosis, expression of the apoptosis-preventing molecules bcl-2 and bcl-xL was studied by immunohistochemistry in skin and bone marrow lesions of mastocytosis patients. In addition, reverse transcription-polymerase chain reaction was used to investigate levels of bcl-2 and bcl-xL mRNA in cutaneous mastocytosis les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 51 publications
(48 reference statements)
2
29
0
2
Order By: Relevance
“…Bax is known to play a preeminent role mediating apoptosis induced by growth factor deprivation (60). Our data reveal that either SCF or IL-3 (acting via BCL-2) or IL-33 (acting via BCLXL) can sustain MC populations exposed to this proapoptotic stress (18,19,58). Whether other causes of apoptosis, such as hypoxia, engage the same pathways remains to be determined.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Bax is known to play a preeminent role mediating apoptosis induced by growth factor deprivation (60). Our data reveal that either SCF or IL-3 (acting via BCL-2) or IL-33 (acting via BCLXL) can sustain MC populations exposed to this proapoptotic stress (18,19,58). Whether other causes of apoptosis, such as hypoxia, engage the same pathways remains to be determined.…”
Section: Discussionmentioning
confidence: 77%
“…In MC, BCL-2 and BCLXL can each promote survival, and inhibition of both essentially eliminates MC in vivo, confirming that they represent the antiapoptotic molecules of dominant physiological relevance for MC (58,59). Both BCL-2 and BCLXL strongly bind and inhibit active Bax, thereby preventing this apoptotic effector from damaging the mitochondrial outer membrane and precipitating cellular demise (41).…”
Section: Discussionmentioning
confidence: 84%
“…This is plausible because activation of Kit by stem cell factor or mutation is known to correlate with expression of Bcl-2 in models of hematopoietic stem cells, natural killer cells, mastocytosis, and melanoma. [25][26][27][28][29][30] Conversely, one study found that Bcl-2 expression was associated with wild-type rather than mutant kit gene expression by microarray analysis. 31 The difference between that study and the current study may be related to the number of patients eval-uated or the different analytical approaches, especially because the results of the current study report the expression of Bcl-2 at the protein level rather than at the RNA level, as reported in the microarray study.…”
Section: Discussionmentioning
confidence: 99%
“…13 In mastocytosis, the expression of Bcl-2 significantly increased while no up-regulation of Bcl-X L was detected. 16 In gastric and colorectal adenocarcinomas, only Bclw was upregulated. 14,15 Besides their selective over-expression in cancer tissues, antiapoptotic Bcl-2 proteins are expressed in healthy tissues in a tissue-selective manner [17][18][19] and function to protect healthy cells.…”
Section: Introductionmentioning
confidence: 99%